A ticket to Russia - Streissguth, Thomas, 1958- (Minneapolis : Carolrhoda Books, 1997)
Examines the geography, history, economy, society, and culture of the Russian Federation, formerly part of the Soviet Union.
Includes bibliographical references (p. 47) and index.
L.A. Recommended Foreign Language
3.6
K-3
Keywords: Russia (Federation) -- Juvenile literature; Russia (Federation); Russia (Federation).